1984
DOI: 10.1002/1097-4679(198407)40:4<884::aid-jclp2270400402>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

The birth seasonality effect in nonschizophrenic psychiatric patients

Abstract: Several studies have suggested that patients with affective, neurotic, and personality disorders are particularly likely to have been born during the early months of the year. They suggest that seasonal factors may play a role in the etiologies of these disorders. However, Lewis and Griffin (1981) Have suggested that the reported seasonal exaggerations in psychiatric patients' birthrates simply may reffect artifacts. We searched for seasonal trends in the birth patterns of neurotics (N = 989), alcoholics (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
2
9
0
1
Order By: Relevance
“…The rate of observed-to-expected schizophrenic births is especially high in December. This December excess has also been reported by other researchers (Templer et al 1978; Watson et al 1982, 1984), and it contradicts the explanation of an artifact as suggested by Lewis and Griffin (1981). (The latter explanation predicts an excess of schizophrenic births in the first quarter of the year and a deficit in the last quarter of the year.…”
Section: Discussionsupporting
confidence: 46%
“…The rate of observed-to-expected schizophrenic births is especially high in December. This December excess has also been reported by other researchers (Templer et al 1978; Watson et al 1982, 1984), and it contradicts the explanation of an artifact as suggested by Lewis and Griffin (1981). (The latter explanation predicts an excess of schizophrenic births in the first quarter of the year and a deficit in the last quarter of the year.…”
Section: Discussionsupporting
confidence: 46%
“…Individuals are considered unexposed when they were conceived during the equivalent period in the subsequent year. We narrowed the definition of the controls explicitly to the equivalent date of birth period in the subsequent year because of possible confounding factors such as a possible relationship between season of birth and addiction disorders, and environmental and social effects such as the Dutch heroin epidemic of the early 1970s [21–26].…”
Section: Methodsmentioning
confidence: 99%
“…London (1998) compared the seasonal birth rates of right-handed and left-handed alcoholic men and found that 66% of the right-handed men were born during the second half of the year, versus 50% of the women and the left-handed men, and at most 52% of men in the general population. Four other studies (Dalen, 1975;Kunugi et al, 1998;Lang and Zur Frage, 1931;Watson et al, 1984b) failed to find any significant seasonal birth pattern among alcoholics.…”
mentioning
confidence: 86%